Two flaws in fractional reserve banking. - Musgrave, Ralph Stephen (Advances in Social Sciences Research Journal, 2020)
The existing bank system, fractional reserve, is inherently risky because it involves accepting deposits while lending out about as much money as has been deposited, and telling depositors their money is safe, which it quite clearly is not and for the simple reason that if a bank makes silly loans, it cannot repay depositors. That problem is currently dealt with via taxpayer backed deposit insurance and billion dollar bail outs for banks. But that state support for banks amounts to preferential treatment for banks relative to other lenders, of which there are several: e.g. peer to peer lenders and trade credit lenders to name just two. That preferential treatment for one type of lender is a misallocation of resources. Second, having a bank lend on your money is just as much a commercial transaction as having a stockbroker lend on or invest your money, and it is not to job of taxpayers to shield those involved in commerce from loss, unless there is an extremely good reason for doing so, which in this case there is not. As for the idea which has become popular of late, namely that commercial banks create the money they lend on rather than intermediate between lenders and borrowers, that is not entirely true as was explained in a Bank of England article (McLeay, 2014). The best solution to the above two flaws in fractional reserve is to abandon all state support for banks while letting those who want their money to be totally safe deposit it with the state, something the people in several countries have actually been free to do for a long time anyway. And that arrangement equals full reserve banking. Earlier expositions of some of the basic ideas in this paper by the author are detailed in an endnote.